Multigene phylogenies and morphological characterization of five new Ophiostoma spp. associated with spruce-infesting bark beetles in China. Issue 4 (April 2016) - Yin, Mingliang; Wingfield, Michael J.; Zhou, Xudong; de Beer, Z. Wilhelm
Abstract: Ophiostoma spp. (Ophiostomatales, Ascomycota) are well-known fungi associated with bark beetles (Coleoptera: Scolytinae). Some of these are serious tree pathogens, while the majority is blue-stain agents of timber. In recent years, various bark beetle species have been attacking spruce forests in Qinghai province, China, causing significant damage. A preliminary survey was done to explore the diversity of the ophiostomatoid fungal associates of these beetles. The aims of the present study were to identify and characterize new Ophiostoma spp. associated with spruce-infesting bark beetles in Qinghai Province, and to resolve phylogenetic relationships of Ophiostoma spp. related to the Chinese isolates, using multigene phylogenetic analyses. Results obtained from four gene regions (ribosomal internal transcribed spacer regions, β-tubulin, calmodulin, translation elongation factor-1α) revealed five new Ophiostoma spp. from Qinghai. These included O. nitidus sp. nov., O. micans sp. nov., and O. qinghaiense sp. nov. in a newly defined O. piceae complex. The other two new species, O. poligraphi sp. nov. and O. shangrilae sp. nov., grouped in the O. brunneo-ciliatum complex. Based on DNA sequence and morphological comparisons, we also show that O. arduennense and O. torulosum are synonyms of O. distortum, while O. setosum is a synonym of O. cupulatum . Highlights: A survey was done on fungal associates of spruce-infesting beetles in Qinghai, China. DNA sequences of four gene regions were used to identify and classify isolates. Five new Ophiostoma species were discovered and described. These taxa grouped in the Ophiostoma piceae and Ophiostoma brunneo-ciliatum species complexes.